Rational Engineering of Polyfluorene based Conjugated Polymers for Sensing and Antibacterial Applications - Chanu, Moirangthem Anita (My University, 2024)
The content of this report entitled “Rational Engineering of Polyfluorene based Conjugated Polymers for Sensing and Antibacterial Applications” is divided into five chapters. The Chapter 1 provides elaborate introduction about the thesis research topics and includes the scope and significance of the subsequent chapters. In the Chapter 2 the development of benzimidazole functionalized polyfluorene homopolymer (PFBZ) and its specific detection of bilirubin (jaundice biomarker) in the real serum samples as well as the preparation of fluorescence paper-based test kits for onsite bilirubin detection is presented.
Iyer, Parameswar Krishnan